2017
DOI: 10.1016/j.foodqual.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethical food choices: Examining people’s Fair Trade purchasing decisions

Abstract: A B S T R A C TFair Trade is a product certification system and social movement that aims to address global supply-chain issues such as forced labour, unsafe working conditions, and unfair pay for workers. The potential for Fair Trade to benefit producers relies directly on consumers' decisions to support these products in their food purchasing choices. An extended Theory of Planned Behaviour (TPB) was used to investigate Fair Trade purchasing among a university student and community sample (N = 178). First, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 29 publications
9
44
2
Order By: Relevance
“…In this research, if Turkish Millennials have a belief that the product is more ethical or healthier, they are more willing to pay a premium price. In the same light, the relationship between WTP a premium and product involvement has been noted by previous studies (Campell et al, 2015;O'Connor et al, 2017;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 74%
“…In this research, if Turkish Millennials have a belief that the product is more ethical or healthier, they are more willing to pay a premium price. In the same light, the relationship between WTP a premium and product involvement has been noted by previous studies (Campell et al, 2015;O'Connor et al, 2017;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown the effect of subjective norms on fair trade consumers (e.g., Ozcaglar‐Toulouse et al, ), but more recent empirical studies have made clear that this is not always the case (e.g., de Leeuw et al, ; O'Connor, Sims, & White, ). For instance, O'Connor et al () found that subjective norms did not significantly contribute to purchase intention among a sample population from Australia, while other factors did have significant effects. In line with this, de Leeuw et al () found that among university students in Luxembourg, subjective norms made a relatively small or even insignificant contribution when traditional TPB factors, moral norms, or past experiences were included in their model.…”
Section: Discussionmentioning
confidence: 99%
“…As incomes in developing countries continue to rise and living conditions improve, demand for meat, dairy, and specialty crops such as fruits, nuts, and vegetables has increased (FAO, 2017). Likewise, consumers in developed countries have developed preferences for specialized products that are marketed as organic, fair-trade, or locally grown (Bellows et al, 2010;Feldmann and Hamm, 2015;O'Connor et al, 2017). Increased demand for food has already strained natural resources resulting in soil erosion, loss of biodiverse landscapes, and pollution of the environment all around the world presenting new challenges in food safety and sustainable food production (Tilman et al, 2011).…”
mentioning
confidence: 99%